An experimental study on the effect of PET fibers on the behavior of exterior RC beam-column connection subjected to reversed cyclic loading. (February 2016) - Marthong, Comingstarful; Marthong, Shembiang
Abstract: An experimental study has been conducted on reduced-scale exterior RC beam-column connections to investigate its behavior due to the addition of Polyethylene terephthalate (PET) fiber-reinforced concrete, i.e., PFRC at the joint region. PET fiber (aspect ratio = 25) of 0.5% by weight of concrete used in the PFRC mix was obtained by hand cutting of post-consumer PET bottles. Three reference specimens were cast and subjected to reverse cyclic loading. Additionally, PFRC specimens were also cast and subjected to similar cyclic displacement. Comparing the results, PFRC specimens improved the damage tolerance, load resisting capacity, stiffness degradation, ductility, and energy dissipation of the specimens. Further, PFRC specimens also presented a lower damage indices and higher principal tensile stresses as compared to the reference specimens. The results obtained gave experimental evidence of the suitability of PET fibers as a discrete reinforcement in substitution of steel fiber for structural use.